ANALISIS PENGARUH SOSIAL EKONOMI TERHADAP PENGELOLAAN SAMPAH DI SUMATERA BARAT (STUDI KASUS DAERAH PERKOTAAN) - Dewi, Nesyana; Adry, Melti Roza (Universitas Negeri Padang, 2020)
This study aims to determine the effect of education, income per capita, age and knowledge on waste management in urban areas West Sumatera. This study uses secondary data in the form of cross section data of urban West Sumatera. Data obtained from BPS- Susenas West Sumatera. This study uses logistic regression analysis. The result of this study indicate that (1) education has not significant effect on waste management in urban areas West Sumatera (2) income per capita has not significant effect on waste managementÂ in urban areas West Sumatera (3) age has not significant effect on waste management in urban areas West Sumatera (4) knowledge has a significant effect on waste management in urban areas West Sumatera